A comparison of four risk models for the prediction of cardiovascular complications in patients with a history of atrial fibrillation undergoing non‐cardiac surgery. (8th July 2019) - McAlister, F. A.; Youngson, E.; Jacka, M.; Graham, M.; Conen, D.; Chan, M.; Szczeklik, W.; Alonso‐Coello, P.; Devereaux, P. J.; ,
Summary: It is unclear how best to predict peri‐operative cardiovascular risk in patients with atrial fibrillation undergoing non‐cardiac surgery. This study examined the accuracy of the revised cardiac risk index and three atrial fibrillation thrombo‐embolic risk models for predicting 30‐day cardiovascular events after non‐cardiac surgery in patients with a pre‐operative history of atrial fibrillation. We conducted a prospective cohort study in 28 centres from 2007 to 2013 of 40, 004 patients ≥ 45 years of age undergoing inpatient non‐cardiac surgery who were followed until 30 days after surgery for cardiovascular events (defined as myocardial injury, heart failure, stroke, resuscitated cardiac arrest or cardiovascular death). The 2088 patients with a pre‐operative history of atrial fibrillation were at higher risk of peri‐operative cardiovascular events compared with the 34, 830 patients without a history of atrial fibrillation (29% vs. 13%, respectively, adjusted odds ratio 1.30 (95%CI 1.17–1.45). Compared with the revised cardiac risk index (c‐index 0.60), all atrial fibrillation thrombo‐embolic risk scores were significantly better at predicting peri‐operative cardiovascular events: CHADS2 (c‐index 0.62); CHA2 DS2 ‐VASc (c‐index 0.63); and R2 CHADS2 (c‐index 0.65), respectively. Although the three thrombo‐embolic risk prediction models were significantly better than the revised cardiac risk index for prediction of peri‐operative cardiovascular events, none of the four models exhibited strong discrimination metrics. There remains a need to develop a better peri‐operative risk prediction model.